Science and Social Inequality : Feminist and Postcolonial Issues - Harding, Sandra G.; Project Muse. (Urbana : University of Illinois Press, 2006)
"In Science and Social Inequality, Sandra Harding makes the provocative argument that the philosophy and practices of today's Western science, contrary to its Enlightenment mission, work to insure that more science will only worsen existing gaps between the best and worst off around the world. She defends this claim by exposing the ways that hierarchical social formations in modern Western sciences encode antidemocratic principles and practices, particularly in terms of their services to militarism, the impoverishment and alienation of labor, Western expansion, and environmental destruction. The essays in this collection--drawing on feminist, multicultural, and postcolonial studies--propose ways to reconceptualize the sciences in the global social order. At issue here are not only social justice and environmental issues but also the accuracy and comprehensiveness of our understandings of natural and social worlds. The inadvertent complicity of the sciences with antidemocratic projects obscures natural and social realities and thus blocks the growth of scientific knowledge. Scientists, policy makers, social justice movements and the consumers of scientific products (that is, the rest of us) can work together and separately to improve this situation."--
Introduction : science and inequality -- The social world of scientific research -- Thinking about race and science -- Seeing ourselves as others see us : postcolonial science studies -- With both eyes open : a world of sciences -- Northern feminist science studies : new challenges and opportunities -- Discriminatory epistemologies and philosophies of science -- Feminist science and technology studies at the periphery of the enlightenment -- Truth, relativism, and science's political unconscious -- The political unconscious of Western science -- Are truth claims in science dysfunctional? -- Does the threat of relativism deserve a panic?
Description based on print version record.
Includes bibliographical references (pages 157-198) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Science -- Social aspects -- Developing countries; Science and civilization; Postcolonialism; Feminism and science; Progress; Sciences -- Aspect social -- Pays en voie de développement.; Sciences et civilisation; Postcolonialisme; Féminisme et sciences; Progrès.; postcolonialism; 08.44 social philosophy; SOCIAL SCIENCE / General; Science -- Social aspects; Science and civilization; Progress; Postcolonialism; Feminism and science; Developing countries; Wissenschaftlicher Fortschritt; Soziale Ungleichheit; Westliche Welt; Sociale rechtvaardigheid; Postkolonialisme; Antiracisme; Feminisme; Wetenschap; Science -- Social aspects -- Developing countries; Science and civilization; Postcolonialism; Feminism and science; Progress